2008
DOI: 10.1038/ncprheum0921
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and musculoskeletal health

Abstract: Vitamin D is critical for calcium homeostasis. Following cutaneous synthesis or ingestion, vitamin D is metabolized to 25(OH)D and then to the active form 1,25(OH)2D. Low serum vitamin D levels are common in the general population and cause a decline in calcium absorption, leading to low serum levels of ionized calcium, which in turn trigger the release of parathyroid hormone, promoting skeletal resorption and, eventually, bone loss or osteomalacia. Vitamin D deficiency is generally defined as a serum 25(OH)D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 72 publications
0
34
0
6
Order By: Relevance
“…Little is known about the effect of sunlight on calcium carbonate deposition in mollusc shells. However, research has revealed the importance of vitamin D, which can be synthesized by exposure to sunlight, on calcium absorption for bone health in humans and other vertebrates (Blunt and Cowan, 1930;Mark et al, 2008;Webb and Holick, 1988;Wolff et al, 2008), and on spicule formation in the gorgonian coral, Leptogorgia virgulata (Kingsley et al, 2001). The effect of pressure on shell morphology of quagga mussels also has not been examined but has been shown to affect growth and normal development of the blue mussel, M. edulis, except at a low temperature of 5°C (Mestre et al, 2009).…”
Section: Functional Consequences Of Shell Morphologymentioning
confidence: 99%
“…Little is known about the effect of sunlight on calcium carbonate deposition in mollusc shells. However, research has revealed the importance of vitamin D, which can be synthesized by exposure to sunlight, on calcium absorption for bone health in humans and other vertebrates (Blunt and Cowan, 1930;Mark et al, 2008;Webb and Holick, 1988;Wolff et al, 2008), and on spicule formation in the gorgonian coral, Leptogorgia virgulata (Kingsley et al, 2001). The effect of pressure on shell morphology of quagga mussels also has not been examined but has been shown to affect growth and normal development of the blue mussel, M. edulis, except at a low temperature of 5°C (Mestre et al, 2009).…”
Section: Functional Consequences Of Shell Morphologymentioning
confidence: 99%
“…La hipovitaminosis D puede producir Sp y debilidad muscular 54 . Se ha establecido la relación entre concentraciones bajas de Vit D como factor de riesgo para desarrollar Sp en ancianos que se expresa en forma de degradación miofibrilar, disminución del recambio proteico y de la secreción de insulina mediada por la hipocalcemia 50,55 .…”
Section: Dietoterapiaunclassified
“…Vitamin D has immunomodulatory steroid hormone properties and directly affects dendritic cell, monocyte, macrophage, B cell, and T cell functions 21,22 ( Fig. 1: vitamin D effects on immune system).…”
Section: Vitamin D and Immunomodulationmentioning
confidence: 99%